Application of Potassium Ferrate in Water Treatment Processes - Olena Ivanenko (Journal of Ecological Engineering, 2020)
The paper presents the results of the investigation of efficiency of potassium ferrate application in water conditioning processes: oxidation of pollutants of different composition by ferrate compounds; clarification of model solutions by coagulation; reduction of corrosive aggressiveness of aqueous solutions. The optimal conditions for water clarification process using potassium ferrate were reagent dose 1 mg·dm-3, pH close to neutral, temperature 20 °C. Oxidation rate of organic substances by potassium ferrate solutions was 50% when applied in concentrations of 15-20 mg·dm-3. Studies on the possible application of the reagent as a steel corrosion inhibitor in neutral aqueous media were conducted. The degree of corrosion protection reached 60%, which indicated the prospect of using iron (VI) compounds as inhibitory additives.